2020
DOI: 10.1371/journal.pbio.3000848
|View full text |Cite
|
Sign up to set email alerts
|

Leiomodin creates a leaky cap at the pointed end of actin-thin filaments

Abstract: Improper lengths of actin-thin filaments are associated with altered contractile activity and lethal myopathies. Leiomodin, a member of the tropomodulin family of proteins, is critical in thin filament assembly and maintenance; however, its role is under dispute. Using nuclear magnetic resonance data and molecular dynamics simulations, we generated the first atomic structural model of the binding interface between the tropomyosin-binding site of cardiac leiomodin and the N-terminus of striated muscle tropomyos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 82 publications
3
46
0
Order By: Relevance
“…However, when 19 N‐terminal residues in Tpm1‐1b(1‐19)Zip were replaced with 26 N‐terminal residues in Tpm1‐1b(1‐26)Zip, we detected changes in Tmod NMR spectra. A similar effect was observed when we studied complexes formed between Lmod TpmBS1 and Tpm1.1 model peptides 40,41 . Although we demonstrated that the major Lmod/Tpm interaction occurs within the first 14 residues of Tpm, additional 7 residues included in the model Tpm peptide led to an NMR spectrum change and a modest, two‐fold increase in binding affinity 41 .…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, when 19 N‐terminal residues in Tpm1‐1b(1‐19)Zip were replaced with 26 N‐terminal residues in Tpm1‐1b(1‐26)Zip, we detected changes in Tmod NMR spectra. A similar effect was observed when we studied complexes formed between Lmod TpmBS1 and Tpm1.1 model peptides 40,41 . Although we demonstrated that the major Lmod/Tpm interaction occurs within the first 14 residues of Tpm, additional 7 residues included in the model Tpm peptide led to an NMR spectrum change and a modest, two‐fold increase in binding affinity 41 .…”
Section: Discussionsupporting
confidence: 80%
“…To validate these results, we also predicted the secondary structure of Lmod2‐TpmBS1, a homologous TpmBS of another member of the Tmod family of proteins, leiomodin 2 (Lmod2). We compared the prediction with the secondary structure of Lmod2‐TpmBS1 in complex with the N‐terminus of Tpm1.1, which we have recently determined by NMR 40 (PDB ID 6UT2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations